Teste de detecção de intervalos aleatórios de silêncio em crianças com história de otite média recorrente - Lapertosa, Claudia Zanforlin (2006)
Introduction: otitis media is an inflammatory disease of middle ear that has greater occurrence on pediatric population, being considered a helth public problem all around the world. Peripheral ans fluctuanting hearing loss may be observed and this may cause a disturbance on the complex auditory stimuli perception, including speech. This altered auditory perception may cause difficulties on sound acoustics representation and on the auditory abilities related to speech in noise recognition, auditory memory, binaural interaction and temporal processing. Objective: to investigate the temporal auditory processing throug random gap detection test in a group of children with recurrent otitis media history on the early year of life. Method: 26 children, aged from 7 of 8 years old, according to one these criteria: otological history of 3 to 4 episodes of otitis media/year on the early years of life; 3 to 4 episodes of otitis media on their first moment life; type B ou C tympanometry at the moment of audiological evaluation. All the children were submited to the following procedures pure tone audiometry, speech audiometry, acoustic immitance measurement and to randm gap detection test (RGDT). Results: data showed RGDT hreshold longer for the frequency of 1000 Hz on the group of children with a type B timpanometry; the same happens with the group that showed abnormal acoustc reflex for 1000 Hz. Averange values for RGDT threshold ere 10 ms, sd of 2,7 ms, median of 10 ms, mode of 10 ms, minimum value was 5 ms an maximum was 15 ms. Compared to Dias (2004) values, the otitis media group showed longer threshold values. Conclusion: recurrent otitis media on early life years may produce a enlargement on the detection of silent intervals threshold